Ovalbumin Based Microlasers - Hong Mai, Hanh (VNU Journal of Science: Mathematics - Physics, 2020)
In this work, biomaterial based microlasers were successfully fabricated by a cost effective, simple and environmental friendly fabrication method. The as-fabricated microlasers were made of biocompatible material including ovalbumin doped Rhodamine B at low weight percentage. The lasers had solid-state spheres with various diameters ranging from 20 µm to over 100 µm. It was shown that inside the spherical cavity which supported whispering gallery mode, a lasing emission was generated with a low threshold of 17.5 µJ/mm 2 , and a high Q-factor of approximately 3000. The remarkable lasing properties of the dye doped ovalbumin microlasers are considered as important bases for their future biological and medical applications.